2019
DOI: 10.7554/elife.44656
|View full text |Cite
|
Sign up to set email alerts
|

TERRA regulate the transcriptional landscape of pluripotent cells through TRF1-dependent recruitment of PRC2

Abstract: The mechanisms that regulate pluripotency are still largely unknown. Here, we show that Telomere Repeat Binding Factor 1 (TRF1), a component of the shelterin complex, regulates the genome-wide binding of polycomb and polycomb H3K27me3 repressive marks to pluripotency genes, thereby exerting vast epigenetic changes that contribute to the maintenance of mouse ES cells in a naïve state. We further show that TRF1 mediates these effects by regulating TERRA, the lncRNAs transcribed from telomeres. We find that TERRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 67 publications
2
29
0
Order By: Relevance
“…Furthermore, a previous study has reported that EZH2 overexpression may correlate with poor prognosis in EC, but this was not found in the TCGA dataset [ 127 ]. EZH2 has been reported to interact with TERF2 and TERF2IP [ 131 ], of the shelterin complex, and also telomeric repeat-containing RNA ( TERRA ) [ 132 , 133 ]. In our survival analysis, AURKA and CCNA2 were identified as markers of unfavourable prognosis ( Table S34 ), which is supported by previous immunohistochemical studies [ 122 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study has reported that EZH2 overexpression may correlate with poor prognosis in EC, but this was not found in the TCGA dataset [ 127 ]. EZH2 has been reported to interact with TERF2 and TERF2IP [ 131 ], of the shelterin complex, and also telomeric repeat-containing RNA ( TERRA ) [ 132 , 133 ]. In our survival analysis, AURKA and CCNA2 were identified as markers of unfavourable prognosis ( Table S34 ), which is supported by previous immunohistochemical studies [ 122 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of the TERT promoter, one of the mostly commonly found non-coding mutations in cancer (Mularoni et al, 2016;PCAWG Consortium, 2020), leads to telomerase upregulation via allelespecific epigenetic alterations involving PRC2 and DNA methylation (Leao et al, 2018;Lee et al, 2019;Stern et al, 2017). The telomeric transcript TERRA associates with PRC2, and in murine iPSCs lacking Tp53, Trf1 depletion results in TERRA-PRC2 recruitment to pluripotency genes (Marión et al, 2019;Montero et al, 2018). Thus, even in situations where telomeres are not critically eroded, epigenetics impinges on telomeres, and telomeres impinge on epigenetics.…”
mentioning
confidence: 99%
“…In contrast to these telomere-related functions, TERRA has recently been shown to be a part of genome-wide mechanisms regulating polycomb recruitment to pluripotency and cell-fate genes in mouse embryonic stem cells [ 95 ]. Earlier observations already suggested the role of the TRF1 shelterin protein in the regulation of pluripotency and tissue reprogramming.…”
Section: Transcripts With Telomere-related Functionsmentioning
confidence: 99%
“…Inspired by these facts, Marion and colleagues (2019) assessed the genome-wide impact of TRF1 down-regulation in a murine model. They showed that upon TRF1 depletion, TERRA levels were greatly increased, correlating with enhanced association with PRC2-controlled (Polycomb Repressive Complex) genes [ 95 ]. Consequently, the lack of TRF1 decreased the expression of pluripotency genes and increased the expression of differentiation genes.…”
Section: Transcripts With Telomere-related Functionsmentioning
confidence: 99%
See 1 more Smart Citation